Mortality and morbidity in COVID-19 orthopedic trauma patients: is early surgery the keystone? - Giorgi, Pietro Domenico (Pan Afr Med J, 2021)
In the pandemic disease caused by SARS-CoV-2 virus, trauma surgery continued the management of patients with fractures. The purpose of the study is to evaluate mortality and morbidity in orthopedic trauma patients surgically treated with a diagnosis of COVID-19 infection, comparing them to a control group of COVID-19 negative. We retrospectively identified patients admitted to our Emergency Room from March 8(th) to May 4(th) 2020 (time frame corresponding to the first wave of the pandemic peak, one of the most severe in the world at that time) with a diagnosis of fracture that were subsequently surgically treated. We applied a dedicated pathway for the management of COVID-19 trauma patients allowed to perform an early surgery and short hospitalization. For each patient included demographics, clinical, laboratory, radiological data and type of treatment for COVID-19 infection were collected. Sixty-five (65) patients were identified. Of those, 17 (6 women and 11 men, mean age 63.41 years old, mean ASA grade 2.35) were COVID-19 positive (study group), while the others were control group (mean age 56.58 years old, mean ASA grade 2.21). In the study group, the preoperative laboratory tests showed leukocytosis in six and lymphopenia in 15 cases. Fourteen patients had a high level of C-reactive protein. Fifteen patients had an abnormal level of D-dimer. The mortality recorded was 5.8% and 4.1% in the study and control group respectively. Perioperative adverse events were registered in 5 cases (29.4%) in the study group and in 8 (16.6%) in the control group (p>0.05). Dedicated COVID-19 trauma pathway with the aim of an early surgery could be key for a better result in terms of mortality and morbidity. Age and ASA grade could represent independent risk factors for perioperative complications.